Very-low-density lipoprotein subfraction composition and metabolism by adipose tissue. - Fisher, R; Miles, J; Kottke, B; Frayn, K; Coppack, S (1997)
Lipoprotein lipase (LPL) plays a pivotal role in very-low-density lipoprotein (VLDL) metabolism. Within the circulation, the VLDL population is heterogeneous with respect to both size and composition. Several studies have investigated the action of LPL in vitro on different VLDL subfractions, but little is known of the action of LPL in vivo. To investigate this, arterial and adipose tissue venous plasma samples were obtained from 16 normal male healthy volunteers (aged 24.4 +/- 1.8 years; body mass index, 23.5 +/- 0.7 kg.m-2) following an overnight fast. VLDL subfractions were isolated (VLDL1 of Sf 60 to 400 and VLDL2 of Sf 20 to 60) and characterized in terms of triacylglycarol (TAG) and apolipoprotein (apo) B, E, CI, CII, and CIII content. The apolipoprotein content of VLDL1 differed from that of VLDL2: the VLDL2 fraction contained significantly more apo B (0.018 +/- 0.004 v 0.011 +/- 0.003 mumol.L-1, p = .001) but the ratios of TAG:apo B and apo CI:B, and CII:B, and CIII:B were significantly higher in VLDL1 (48,200 +/- 7,980 v 13,860 +/- 2,420, 22.7 +/- 5.5 v 12.5 +/- 2.2, 45.0 +/- 6.3 v 14.9 +/- 2.0, and 0.434 +/- 0.077 v 0.357 +/- 0.054, respectively, molar ratios, all P < .05). The venous blood draining an adipose tissue depot contained less VLDL1-TAG than arterial blood (328 +/- 68 v 381 +/- 83 mumol.L-1, respectively, P < .01), whereas VLDL2-TAG exhibited an opposite tendency (199 +/- 46 v 172 +/- 31 mumol.L-1, NS). Concentrations of VLDL1-apo B, -apo CII, and -apo CIII were significantly less in adipose tissue venous blood compared with arterial blood (0.011 +/- 0.004 v 0.013 +/- 0.004, 0.38 +/- 0.08 v 0.43 +/- 0.10, and 1.33 +/- 0.35 v 1.58 +/- 0.38 mumol.L-1, respectively, all P < .05). These studies demonstrated novel differences in VLDL1 and VLDL2 in terms of composition and metabolism by human adipose tissue LPL in vivo.